1995
DOI: 10.1063/1.871461
|View full text |Cite
|
Sign up to set email alerts
|

Helicon wave excitation with helical antennas

Abstract: Components of the wave magnetic field in a helicon discharge have been measured with a single-turn, coaxial magnetic probe. Left- and right-handed helical antennas, as well as plane-polarized antennas, were used; and the results were compared with the field patterns computed for a nonuniform plasma. The results show that the right-hand circularly polarized mode is preferentially excited with all antennas, even those designed to excite the left-hand mode. For right-hand excitation, the radial amplitude profiles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
115
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 120 publications
(127 citation statements)
references
References 14 publications
12
115
0
Order By: Relevance
“…reasons not yet known, as reported earlier 10 . The N antenna was expected to give a plane polarized wave, created by a linear combination of the +1 and -1 modes; but in practice it excites only the +1 mode in both directions 10 .…”
Section: B Antennassupporting
confidence: 55%
See 3 more Smart Citations
“…reasons not yet known, as reported earlier 10 . The N antenna was expected to give a plane polarized wave, created by a linear combination of the +1 and -1 modes; but in practice it excites only the +1 mode in both directions 10 .…”
Section: B Antennassupporting
confidence: 55%
“…2. A detailed explanation of the proposed coupling mechanism 16 for these antennas has been given by Light and Chen 10 . Since the free space wavelength at the frequency of interest for this experiment is much larger than any dimension of the antennas, we can assume that the current reaches all parts of the antenna simultaneously.…”
Section: B Antennasmentioning
confidence: 99%
See 2 more Smart Citations
“…Applications include plasma opening switches [2], pulsed ion beam propagation across Bo [3], helicon waves [4], electrodynamic tethers in space [5], dissipation processes in narrow current sheets undergoing reconnection [6], plasma releases [7], and wings behind small asteroids in the solar wind [8]. Basic physics experiments have demonstrated that pulsed EMHD currents in magnetized plasmas are transported by whistler waves [9-111.…”
Section: Introductionmentioning
confidence: 99%